The new additive to petrol - Ал-Хаддад, Амир Т. Джасим; Киселёва-Логинова, Екатерина Валерьевна; Ижак, Андрей Викторович; Исак, Александр Демьянович; Попов, Евгений Вадимович (Technology audit and production reserves, 2013)
The multifunctional oxygen-containing additive (Dispersant PME-T) to motor petrol and diesel fuel was developed. The additive is resistant to thermal influence, keeping its high surfactant properties, and also allows to homogenize the system of hydrocarbon-water-alcohol. The formed thin fuel dispersion is well combusted in the engine, thus greatly reduces negative emissions into the atmosphere, according to the environmental European standards. The intermolecular interaction of alcohols with ethanolamines in the presence of nonionic surfactant with the formation of the stable system was proved. Oxyethylated long-chain alcohols, nonylphenol ethoxylates, alkenyl succinimides can be used as nonionic surfactants. Stability of the system is reduced at temperatures above 50°C and broken with the formation of initial substances. Such system increases the hazard class (moderately hazardous substances); it is human friendly and biodegradable.